2002
DOI: 10.1136/gut.51.6.803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of appendicectomy on the course of ulcerative colitis

Abstract: Background: Appendicectomy reduces the risk of having ulcerative colitis. However, its effect on the natural history of ulcerative colitis remains uncertain. Aim: To determine whether appendicectomy reduces the overall severity of ulcerative colitis. Patients and methods: Appendicectomy status and smoking habits were specified by direct interview in 638 patients seen consecutively between 1997 and 2000. Severity of ulcerative colitis was assessed by reviewing therapeutic needs from the onset of colitis. Additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
0
6

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(72 citation statements)
references
References 28 publications
2
64
0
6
Order By: Relevance
“…Although the pathogenesis of UC remains unclear, clinical evidence suggests that appendectomy may protect against the onset and severity of UC (21,22), suggesting that the appendix may be a priming site for UC (4). Hence, the role of the appendix in the pathogenesis of UC should be clarified, as reported by Matsushita et al (23).…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathogenesis of UC remains unclear, clinical evidence suggests that appendectomy may protect against the onset and severity of UC (21,22), suggesting that the appendix may be a priming site for UC (4). Hence, the role of the appendix in the pathogenesis of UC should be clarified, as reported by Matsushita et al (23).…”
Section: Discussionmentioning
confidence: 99%
“…Patients who have been appendectomized have a lesser risk of developing UC. Moreover, in the few appendectomized patients who develop UC, disease course is less severe, with a decreased need of colectomy compared to non-appendectomized patients [3,4] . Of note, the effects of smoking and appendectomy are additive [4] .…”
Section: Introductionmentioning
confidence: 99%
“…The human appendix has long been recognized as a vestigial remnant. Although the pathogenesis of UC has not been fully clarified, clinical evidence has revealed the protective role of appendicectomy on onset and severity of UC [2,3], indicating the appendix as a priming site for UC [4]. Experimental studies of murine models have also shown that the appendix may serve a central role in antigen sampling and immunological signaling [5].…”
mentioning
confidence: 99%